Cerai Gugat Akibat Kekerasan dalam Rumah Tangga : Studi Kasus di Pengadilan Agama Bawean - Juaeriyah Juaeriyah; M. Halilurrahman (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Divorce is one of the undesirable things for both husband and wife in a marriage. One of the factors that often triggers divorce is Domestic Violence. In the Decision of the bawean Religious Court, the panel of judges granted the Plaintiff's lawsuit. Divorce lawsuits due to domestic violence are caused by several factors, including arguments, economic problems, infidelity, which occur in the Bawean religious court, resulting in physical violence such as hitting, kicking, slapping. Divorce due to domestic violence at the Bawean Religious Court where the divorces that occurred in 2023 in July, August, and October yesterday, there were 4 cases of divorce due to domestic violence and in 2024 in July alone there was 1 case and all of them were granted because mediation was not successful because the Plaintiff could no longer forgive the Defendant and the Plaintiff insisted on divorcing the Defendant.